Reframing the high-technology landscape in Greece: Empirical evidence and policy aspects - Antonios Angelakis (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2022)
Purpose: The major purpose of the paper is to explore, identify and highlight the general and specialized (sector-specific) long-term technology trends following the evolution of technology-intensive sectors in Greece during the last years. In a similar vein, sectoral differentiations have been identified and highlighted (e.g. evolution, growth, size distribution, industrial dynamics) as an analytical dimension of innovative activity across the high-technology sectoral domain. Design/methodology/approach: The paper methodology consists of a systematic review of primary data collected through the Eurostat/SBS database and the SME Performance Review 2022, as one of the major tools the European Commission uses to monitor and assess countries' progress in implementing the Small Business Act (SBA). The methodological approach of the paper involves the mapping of sector-specific trends in terms of technology-intensive categories, size classes and underlying sectoral characteristics and dynamics trends. Findings: The exploration of detailed and long-term data within the landscape of technology-intensive sectors in Greece, provides a clearer picture for the upward and downward trends, the sector-specific differentiations and the upcoming challenges. High-tech enterprises constitute a considerably important part of the country's productive base with gradually increasing trends in all relevant categories. This is further motivated by the development of start-ups and spin-offs in several fields of higher technological specialization ('deep tech'). Research limitations/implications: It is widely accepted that aggregated technology growth is a long-term and multi-level process within an economy. Further research regarding the actual and potential spillover effects of technology sectors across the wider economy constitutes an important area of further research. The paper provides a multi-dimensional analytical framework to identify sector-based technological and industrial underlying dynamics and understand long-term sectoral characteristics and trends within the high-tech industry evolution in Greece. Originality/value: The paper provides an analytical approach to explore the underlying industrial dynamic trends within the technology-intensive sectors in Greece. The exploration of detailed and long-term data within the landscape of technology-intensive sectors in Greece provides an overall view of the underlying technology-intensive sectors' dynamics, the sector-specific differentiations, the upcoming challenges and the innovation policy implications.
Keywords: O14; O32; O33; O38; 330; Innovation; High- technology sectors; Knowledge intensive services; Technology and innovation policy; Technology ecosystems; VC funding; Scale-up capital